Evaluation of a Chlamydia trachomatis-specific, commercial, real-time PCR for use with ocular swabs - Harry Pickering (Parasites & Vectors, 2018)
Abstract Background Trachoma, the leading infectious cause of blindness worldwide, is caused by conjunctival Chlamydia trachomatis infection. Trachoma is diagnosed clinically by observation of conjunctival inflammation and/or scarring; however, there is evidence that monitoring C. trachomatis infection may be required for elimination programmes. There are many commercial and ‘in-house’ nucleic acid amplification tests for the detection of C. trachomatis DNA, but the majority have not been validated for use with ocular swabs. This study evaluated a commercial assay, the Fast-Track Vaginal swab kit, using conjunctival samples from trachoma-endemic areas. An objective, biostatistical-based method for binary classification of continuous PCR data was developed, to limit potential user-bias in diagnostic settings. Methods The Fast-Track Vaginal swab assay was run on 210 ocular swab samples from Guinea-Bissau and Tanzania. Fit of individual amplification curves to exponential or sigmoid models, derivative and second derivative of the curves and final fluorescence value were examined for utility in thresholding for determining positivity. The results from the Fast-Track Vaginal swab assay were evaluated against a commercial test (Amplicor CT/NG) and a non-commercial test (in-house droplet digital PCR), both of whose performance has previously been evaluated. Results Significant evidence of exponential amplification (R 2 > 0.99) and final fluorescence > 0.15 were combined for thresholding. This objective approach identified a population of positive samples, however there were a subset of samples that amplified towards the end of the cycling protocol (at or later than 35 cycles), which were less clearly defined. The Fast-Track Vaginal swab assay showed good sensitivity against the commercial (95.71) and non-commercial (97.18) tests. Specificity was lower against both (90.00 and 96.55, respectively). Conclusions This study defined a simple, automated protocol for binary classification of continuous, real-time qPCR data, for use in an end-point diagnostic test. This method identified a population of positive samples, however, as with manual thresholding, a subset of samples that amplified towards the end of the cycling program were less easily classified. When used with ocular swabs, the Fast-Track Vaginal swab assay had good sensitivity for C. trachomatis detection, but lower specificity than the commercial and non-commercial assays it was evaluated against, possibly leading to false positives.